Causes of death in people with liver cirrhosis in England compared to the general population: a population-based cohort study - Ratib, Sonia; Fleming, Kate M.; Crooks, Colin J.; Walker, Alex J.; West, Joe (Nature Publishing Group, 2015)
Introduction Liver cirrhosis is increasing worldwide and associated with high mortality. Precise estimates of cause-specific mortality compared to the general population, by underlying aetiology, are lacking. Such information may demonstrate areas where therapeutic interventions can be targeted. Method We identified from the linked Clinical Practice Research Datalink (CPRD) and English Hospital Episode Statistics adults with an incident diagnosis of liver cirrhosis linked to the Office for National Statistics between 1998 and 2009. Age-matched controls from the CPRD general population were selected. We calculated the cumulative incidence (adjusting for competing risks) and excess risk of death by 5-years from diagnosis for different causes of death, stratified by aetiology and stage of disease. Results 5118 patients with cirrhosis were matched to 152,903 controls. Amongst compensated patients, the 5-year excess risk of liver-related death was higher than that of any other cause of death for all patients except those of unspecified aetiology. For example, those of alcohol aetiology had 30.8% excess risk of liver-related death (95%CI 27.9%, 33.1%) compared to 9.9% excess risk of non-liver related death. However, patients of unspecified aetiology had a higher excess risk of non-liver related compared to liver-related death (10.7% vs. 6.7%). This was due to a high excess risk of non-liver neoplasm death (7.7%, 95%CI 5.9%, 9.5%). All decompensated patients had a higher excess of liver-related mortality than any other cause. Conclusion In order to reduce associated mortality amongst people with liver cirrhosis, patients’ care pathways need to be tailored depending on aetiology and stage of disease.